A short-term, exploratory randomized controlled trial on the safety and feasibility of intraoperative raltitrexed peritoneal chemotherapy in laparoscopic radical resection for advanced colorectal cancer - Jin, Haipeng; Yao, Jun; Wei, Zhiping; Zhou, Wenqiang; Chen, Chen; Ying, Rongbiao (Frontiers in Surgery, 2026)
BackgroundPatients with advanced colorectal cancer (CRC) with primary tumor stage T3 or T4 are at increased risk of peritoneal metastasis. The safety and feasibility of combining radical resection with intraoperative intraperitoneal perfusion chemotherapy (IPC) using raltitrexed in this population warrant further investigation.MethodsIn this single-center, exploratory randomized controlled trial, 60 patients with advanced CRC (T3, T4) scheduled for laparoscopic radical resection were randomly assigned to receive either intraoperative raltitrexed IPC (n = 30) or surgery alone (control, n = 30). The primary endpoints were safety and feasibility. Toxicity profiles (hematologic, renal, hepatic), postoperative complications within 14 days, and procedural feasibility were compared between groups. Short-term tumor marker levels [carcinoembryonic antigen [CEA] and carbohydrate antigen 19-9 [CA19-9]] were assessed as exploratory endpoints, measured preoperatively and at three months postoperatively, with recurrence or metastasis events recorded within the same period.ResultsThe IPC procedure was successfully completed in all assigned patients, confirming procedural feasibility. No significant between-group differences were observed in postoperative hematological toxicity, nephrotoxicity, or complication rates. Transaminase elevations (ALT/AST) on postoperative day seven were transient and mild in both cohorts, with a more marked yet clinically manageable increase in the IPC group. At the three-month follow-up, no significant between-group differences were found in tumor marker levels or recurrence rates. Within-group analyses, however, demonstrated a significant decrease in CEA in the IPC group [mean change: −2.23 ± 4.68 ng/mL (95% CI: 0.48–3.98); P = 0.014] and a significant increase in CA19-9 in the control group [mean change: +3.33 ± 7.07 U/mL (95% CI: 0.69–5.97); P = 0.015].ConclusionsFor patients with advanced CRC (T3/T4), laparoscopic radical resection combined with intraoperative raltitrexed IPC is feasible and exhibits an acceptable short-term safety profile. Observed short-term changes in tumor markers are considered exploratory findings and require validation in subsequent, large-scale prospective studies with extended follow-up periods.